Top performer award - Esguerra, Trixia (Animo Repository, 1996)
Trixia Esguerra, a senior Bachelor of Science in Accountancy student, was given the Top Performer Award by the Sycip, Gorres and Velayo (SGV) auditing firm in the Audit Practicum Sessions. The Audit Practicum is an optional subject for Accountancy majors who go through on-the-job and actual business accounting work with the SGV firm for 87 hours.